Elements of the ideology of the Sixtiers — members of the Russian revolutionary community of the 1860s - Victor Kirillov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article analyzes the ideology of the Sixties – members of the Russian revolutionary community of the late 1850s – 1860s. A revolutionary community means a set of ideologically close personalities and associations with revolutionary views; it makes possible to examine members of the revolutionary underground and people sympathizing with revolutionary views as one community. Due to the fact that definitions of the Sixties as revolutionary democrats, Narodniks, nihilists, etc. are common in historiography, the article proposes to look at their ideology as a non-hierarchical, eclectic combination of different views, concepts and ideas, among which there were no main ideas. The author of the article identifies six main elements of the ideology of the Sixties: the denial of the old regime (which presupposed anti-conservative views, as well as the prevalence of the nihilism subculture), socialist orientation (from the strict theory of “Russian socialism” to abstract sympathies for the very idea of socialism), “craving for the people” (which foreshadowed the ideology of revolutionary Narodnichestvo of the 1870s), democratic ideals (which mainly assumed egalitarianism, the idea of equality of all members of society, which resulted in interest and support for the women’s movement, the creation of communes for living together and everyday life), enlightenment (expressed in the cult of science and knowledge, educational work among the intelligentsia), faith in the proximity of the revolution (a specific feature of the Sixties, which manifested itself in anticipation of an imminent mass popular uprising). The research is based on a complex of various sources (memoirs, journalism, investigative testimony), according to which it is possible to identify the views of both well-known publicists of democratic magazines and the emigrant press, as well as members of underground revolutionary circles.